Design and Evaluation of the Finnish Basic Income Experiment - Kari Hämäläinen; Jouko Verho (Center for Economic Studies and ifo Institute (CESifo), 2022)
The Finnish basic income experiment was an ambitious effort to study basic income in a Nordic welfare state. This paper describes the planning, implementation and scientific evaluation of the experiment. The randomized treatment group was paid a guaranteed monthly income, which had no impact on disposable income while a person was unemployed but provided a substantial increase in work incentives. We extend previous evaluations by examining the heterogeneity of incentive changes and employment responses across households. Our results reveal improvements in employment only for couples with children, providing an interesting contrast to other in-work credit programs.
Keywords: C93; H55; I38; J65; 330; employment; field experiment; social insurance; unemployment benefits